Experiential learning: - Caudillo, Dora Yessica (Qualitative and Quantitative Methods in Libraries; Vol 11 No 1 (2022): March issue 2022, 2022)
Meaningful learning is considered an active methodology that allows acquiring knowledge from living the experience. An educational program based on the principles of Information Culture promotes, among diverse purposes, the access to knowledge from the visit to libraries in Southern California. The geographical proximity of both sides of the border between the United States (San Diego, California) and Mexico (Tijuana, Baja California), has allowed to strengthen relations between public and university libraries to give access to information and knowledge to students of the higher level through experiential experience.